Characteristics of work related asthma: results from a population based survey. Issue 6 (23rd February 2006) - Breton, C V; Zhang, Z; Hunt, P R; Pechter, E; Davis, L
Abstract : Objectives: Many risk factors for asthma have been investigated, one of which is the workplace. Work related asthma is a frequently reported occupational respiratory disease yet the characteristics which distinguish it from non-work related asthma are not well understood. The purpose of this study was to examine differences between work related and non-work related asthma with respect to healthcare use and asthma control characteristics. Methods: Data from the Massachusetts Behavioral Risk Factor Surveillance System for 2001 and 2002 were used for this analysis. Work related status of asthma was determined by self-report of ever having been told by a physician that asthma was work related. Healthcare measures evaluated were emergency room visits and physician visits for worsening asthma and for routine care. Characteristics of asthma control evaluated were frequency of asthma symptoms, asthma attacks, difficulty sleeping, and asthma medication usage in the last 30 days and limited activity in the past 12 months. Results: The prevalence of lifetime and current asthma in Massachusetts were 13.0% and 9.2%, respectively. Approximately 6.0% (95% CI 4.8 to 7.3) of lifetime and 6.2% (95% CI 4.7 to 7.8) of current asthma cases were work related. In the past 12 months, individuals with work related current asthma were 4.8 times (95% CI 2.0 to 11.6) as likely to report having an asthma attack, 4.8 times (95% CI 1.8 to 13.1) as likely to visit the emergency room at least once, and 2.5 times (95% CI 1.1 to 6.0) as likely to visit the doctor at least once for worsening asthma compared to individuals with non-work related asthma. Conclusions: Work related asthma is associated with increased frequency of asthma attacks and use of healthcare services. A better understanding of factors that contribute to differences in healthcare use and asthma control is needed to improve prevention and control strategies for individuals suffering from the disease.